TACE-Sorafenib With Thermal Ablation Has Survival Benefits in Patients With Huge Unresectable Hepatocellular Carcinoma - Wu, Ying; Qi, Han; Cao, Fei; Shen, Lujun; Chen, Shuanggang; Xie, Lin; Huang, Tao; Song, Ze; Zhou, Danyang; Fan, Weijun (Frontiers in Pharmacology, 2020)
Purpose: To compare the effectiveness and safety of transarterial chemoembolization (TACE) combined with sorafenib and with/without thermal ablation in patients with huge hepatocellular carcinoma (HCC). Materials and Methods: This retrospective study examined 50 patients with huge unresectable HCC treated from 01/2009 to 12/2015, 28 patients received TACE-sorafenib and 22 patients received TACE-sorafenib-thermal ablation. Overall survival (OS), progression-free survival (PFS), and AEs were compared. Results: The median follow-up was 13.5 (range, 4.2-96.7) months. The median OS was significantly longer in the TACE-sorafenib-thermal ablation group (20.8 vs. 10.4 months, P=0.003). The median PFS of the ablation and no ablation groups were 4.3 vs. 7.1 months (P=0.546). Treatment choice was an independent predictor of OS (P=0.004). No drug-related grades 4-5 adverse events or permanent adverse sequelae were recorded. Conclusion: TACE-sorafenib-thermal ablation provided extended long-term OS to patients with huge unresectable HCC and may be a better choice than TACE-sorafenib.